Fortification of staple foods with calcium: a novel costing tool to inform decision making. Issue 1 (31st March 2022) - Palacios, Alfredo; Rojas‐Roque, Carlos; Balan, Dario; Sosa Estani, Isabela; Belizán, José M.; Cormick, Gabriela; Augustovski, Federico
Abstract: Low calcium intake and its impact on maternal and child health are a major concern in low‐ and middle‐income countries. Given the low calcium in diet, as well as the low adherence and acceptability of calcium pills in those settings, the discussion about policies to increase calcium intake has moved toward staple food fortification strategies. Nevertheless, there is scarce information on the economic feasibility of implementing these strategies. We aimed to design and propose a novel costing tool to estimate the cost of the flour fortification with calcium by carrying out a literature review about costing studies for staple food fortification programs and costing tools previously developed. A deliberative meeting with stakeholders was held to discuss and face‐validate the conceptual framework proposed. We showed the costing tool application for the case of Costa Rica (a country with a population with low calcium intake), including the absolute cost of the staple food fortification production process, the incremental cost of fortification according to the public/private sector, and the incremental cost by target population. This open‐source and publicly available costing tool can be useful to inform policymaking in countries considering the implementation of staple food fortification programs. Abstract : This study is part of a research project that aimed to evaluate the effectiveness, safety, cost‐effectiveness and affordability of water and staple food fortification with calcium in low‐and middle‐income countries (LIMCs). The application of the costing tool to the case of Costa Rica (a country with a population with low calcium intake) is shown, including the absolute cost of the staple food fortification production process, the incremental cost of fortification according to the public/private sector, and the incremental cost by target population.